Pelatihan Public Speaking Role-Play untuk Pengembangan Diri Santri di Pesantren Fauzan Garut - sopiah, Sopi; Suseno, Novie Susanti (Penerbit Goodwood, 2025)
Purpose: The primary aim of this program is to improve the students’ public speaking skills, enabling them to confidently deliver messages and communicate effectively in front of others. Methodology: The program was conducted in a structured manner, beginning with an intensive public speaking training session, followed by weekly mentoring over a month. The training covered voice control, body language, and message delivery strategies. The role-play-based mentoring was held in two main practice rooms, the dakwah and sholawat/qoriah rooms, providing realistic environments for students to practice. Results: The program successfully increased participants' self-confidence, as evidenced by their enhanced willingness to speak in public, deliver religious messages, and engage in social interactions. This service has proven to be effective in improving students' communication skills, which are crucial for both religious preaching (dakwah) and everyday social interactions. Conclusion: In conclusion, the structured combination of public speaking training and role-play-based mentoring is an effective approach to developing self-confidence and communication skills among Islamic boarding school students. Future improvements, such as the integration of audiovisual tools, may further strengthen the program’s outcomes. Limitations: The activity did not incorporate audio-visual media, which slightly hindered the impact of some presentation methods. Future sessions may benefit from using tools like projectors and microphones to enhance learning and practice. Contribution: This program has positively impacted the participants by enhancing their public speaking abilities, which will be beneficial for both their religious and social engagement.